1999
DOI: 10.1111/j.1745-4557.1999.tb00562.x
|View full text |Cite
|
Sign up to set email alerts
|

HEADSPACE GAS CHROMATOGRAPHY AND SENSORY ANALYSES OF BUCKWHEAT STORED UNDER CONTROLLED ATMOSPHERE1

Abstract: The composition of volatile components in freshly-milled buckwheat jlour producedfrom seed stored under controlled atmospheres (97% N2. 1.5% 0, and 1.5% CO,) for I year was studied using capillary gas chromatography, mass spectrometry, sniffing port analysis, and sensory evaluation. Twenty-five volatiles were identified from over I00 compounds removed fiom the flour by a novel dynamic headspace technique and separated by capillary gas chromatography. Eighteen odor-active regions were detected but none were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…For example, the concentration of the major buckwheat volatiles decreased with storage of the seed under low O 2 and high CO 2 levels. The content of 2 of the odor‐active volatiles, hexyl acetate and 1‐hexanol, however, increased up to 4‐fold in samples stored under controlled atmosphere (97% N 2 , 1.5% O 2 , and 1.5% CO 2 ) for 60 wk (Mazza and others 1999). Relatively low storage temperatures were suitable for preserving the flavor of the buckwheat flour and the total amount of flavor components decreased with increased storage period (Kawakami and others 2008; 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the concentration of the major buckwheat volatiles decreased with storage of the seed under low O 2 and high CO 2 levels. The content of 2 of the odor‐active volatiles, hexyl acetate and 1‐hexanol, however, increased up to 4‐fold in samples stored under controlled atmosphere (97% N 2 , 1.5% O 2 , and 1.5% CO 2 ) for 60 wk (Mazza and others 1999). Relatively low storage temperatures were suitable for preserving the flavor of the buckwheat flour and the total amount of flavor components decreased with increased storage period (Kawakami and others 2008; 2009).…”
Section: Introductionmentioning
confidence: 99%
“…OAV is a ratio between actual concentration in the sample and the threshold concentration needed for detection by human nose. Nonanal and octanal could also be important for the aroma of buckwheat because of low odor threshold values in water (Mazza et al 1999). Yajima et al (1983) identified 209 compounds in boiled buckwheat flour; however, none of them possessed the characteristic aroma of boiled buckwheat flour.…”
mentioning
confidence: 99%
“…Aldehydes, alcohols, ketones, benzene derivatives, hydrocarbons, acids, esters and sulphur-containing compounds are the main volatile compounds present in cereals. Among the different volatile compounds in buckwheat, salicyl aldehyde was identified as major aroma compound besides that nonanal 13 , octanal and hexanal detected in smaller quantities 1 . Dehusking and polishing steps in grain processing not only improve the sensory and edible quality of grain but also yield the main product and by-products.…”
Section: Identification and Quantification Of Volatile And Phenolic Cmentioning
confidence: 96%
“…However, because its seeds are structurally and chemically resembles as cereal grains, buckwheat is classed with the cereal groups. It is originated in the mountain regions of southern China and produced in many parts of the world and has long been an important part of the human diet 1 . The products developed from buckwheat have attained an excellent reputation for its nutritious qualities in the human diet.…”
Section: Introductionmentioning
confidence: 99%